A Green and Structure-Controlled Approach to the Generation of Silicone Rubber Foams by Means of Carbon Dioxide. Issue 1 (January 2016) - Xu, Hao; He, Yunchuan; Liao, Xia; Luo, Tinggang; Li, Guangxian; Yang, Qi; Zhou, Chuanjian
Silicone rubber foams were successfully generated by environmentally friendly blowing agent, supercritical carbon dioxide (scCO2 ), in this research. Firstly, the effect of the saturation time on the cellular structure was investigated. The diffusion of scCO2 into the rubber matrix would be enhanced thus decreasing the viscosity as increasing the saturation time. It would further promote the cell growth, which has a close connection with the cellular structure. After that, the effect of pre-curing time on cellular morphology of silicone rubber foams was further researched in detail. When increasing pre-curing time in the short time range, cell nucleation would be affected more than cell growth in the foaming process. If continuously increasing pre-curing time, both cell nucleation and growth would be restricted thus resulting in the formation of silicone rubber foams with small cell density and small cell size. This investigation not only provided a green way to produce silicone rubber foams, but also guided us to control cellular morphology via the saturation time and pre-curing time.